Research Progress on a Wide and Narrow Row Cropping System for Crops - Liqun Tang; Jian Song; Yongtao Cui; Honghuan Fan; Jianjun Wang (Agronomy, 2025)
Optimizing planting density enhances light capture, improves air circulation, and promotes more efficient resource utilization, ultimately leading to increased crop productivity. It facilitates uniform growth, maximizes land use efficiency, reduces nutrient competition, and supports sustainable weed management, thereby improving yield and resource use efficiency. The wide and narrow row cropping (WNRC) system is an optimized planting method that adjusts the row spacing strategically to enhance crop growth and productivity. This study reviews the development and implementation of WNRC technology, focusing on its effects on crop growth, development, and environmental optimization. (1) Crop growth and environmental optimization: Modifying the row spacing in WNRC enhances light interception, air circulation, and the soil moisture distribution, creating an optimized growth environment that improves the photosynthetic efficiency and water use. (2) Genetic variation and yield performance: The performance of different crop varieties in WNRC systems varies, with specific varieties showing better adaptation to the altered spatial arrangement, leading to improved growth uniformity and higher yields. (3) Weed management: The planting density is optimized, reducing the need for herbicides and fostering more sustainable weed control methods. (4) Efficient input management: WNRC systems enhance the uniform application of fertilizers and pesticides, optimizing nutrient uptake, minimizing input wastage, and lowering the environmental impact. While WNRC offers substantial advantages in yield enhancement and resource optimization, challenges remain in adapting this technology to diverse cropping systems and environmental conditions. Further research is required to refine WNRC for specific regions and crops, ensuring its long-term agronomic and ecological benefits.